TELAAH TEORITIS-EMPIRIS POTENSI PANTAI HUNIMUA-LIANG PROVINSI MALUKU - Ubaiyana, Ubaiyana (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
This study aims to find the potential, solutions, and strategies in reconstructing the development of Hunimua Beach. The research method used three methods of data collection, namely interviews, observation, and literature study, which analyzed in a descriptive-qualitative-analytical way. Results of the study show that Hunimua beach has great potential to become a regional priority tourist destination and even Indonesia’s priority. The strengths of Hunimua Beach are easy accessibility, support for other tourist attractions, being located in traditional villages, and extensive tourist sites. However, in maximizing the potential of Hunimua Beach, various obstacles need to be addressed immediately, namely the Hunimua Land claim, internal problems between the village and the region, and the weak support from the central government.